Analisis Pengaruh PMDN dan PMA terhadap Kesempatan Kerja di Indonesia - Eliza, Eliza (Jurusan PIPS FKIP UMMY Solok, 2016)
Increase activity of economy in all of kainds sector would give effect direct or indirect to creat work opportunity. Essentially part of invest very important to support development of region. Invest was factor to formation and creat income of region and have part that very important of region economy. Invest could expansion work opportunity. Result of research show PMDN and PMA do test partially and simultan have good effect and significant to work opportunity in Indonesia. It’s mean increase to work opportunity have relation to invest as indicator of development. This case connected to income and work opportunity and development would way goodly